Pelatihan Penguatan Partisipasi Masyarakat dalam Perencanaan Pembangunan di Desa Andomesinggo Kecamatan Besulutu Kabupaten Konawe - Tanzil; Juhaepa; Peribadi; Anggraini, Dewi; Kasim, Syaifudin Suhri (Indonesian Journal of Community Services, 2023)
The purpose of this community service activity is to conduct training on strengthening community participation in village development planning. This community service activity was carried out in Andomesinggo Village, Besulutu District, Konawe Regency. This community service activity was carried out in two stages; the first stage was to provide knowledge about the importance of community involvement in development planning to encourage successful development. This stage was carried out using the method of lectures and discussions with the training participants. Furthermore, a direct field review was conducted with the trainees to understand the problems faced in development planning. This service activity has received approval to be integrated with the Village Development Program in Andomesinggo Village, Besulutu District, Konawe Regency.